Analisis Resiko K3 Pekerja Menggunakan Metode Hazard and Operablity (HAZOP) - Qurthuby, Muhammad; Satriardi, Satriardi; Hendra Saputra, Yohanes (SURYA TEKNIKA, 2024)
PT. Pipa Mas Putih is a company engaged in the oil and gas sector. In the production process at PT. Pipa Mas Putih there are still employees who do not pay attention to work procedures, do not use complete PPE, such as not using project helmets, safety shoes, masks, goggles and ear plugs. Until now there are still work accidents. Based on the results of work accident interviews that often occur at PT. Pipa Mas Putih namely, collided, splashed particles in the eye, slipped, squeezed and electrocuted. Hazard and Operability (HAZOP) is a method used to control the risk of work accidents by conducting a risk assessment, which aims to prevent work accidents that can occur. This research was conducted to identify hazard levels that can reduce the level of accidents that can occur in the production area of ​​PT. White Mas pipe. The results of research using the HAZOP method are 1 (one) hazard with very high consequences and 7 (seven) hazards that are classified as having high risk. The steps to reduce the level of risk include providing training to employees and socializing to workers so that they always work according to SOPs and use complete PPE, always carry out toolbox meetings and always prioritize OHS in carrying out work activities.